COVID-19 vaccine uptake among family caregivers of people with dementia: The role of attitudes toward vaccination, perceived social support and personality traits - Bruno, Francesco; Malvaso, Antonio; Chiesi, Francesca; Laganà, Valentina; Servidio, Rocco; Isella, Valeria; Ferrarese, Carlo; Gottardi, Federica; Stella, Eloisa; Agosta, Federica; Filippi, Massimo; Lorenzo, Raffaele Di; et al. (Frontiers in Psychology, 2022)
People with dementia have an increased risk of contracting severe forms of COVID-19. Although in worldwide vaccination programs priority has been given to older people, having taken the vaccine does not totally eliminate the risk of contracting COVID-19 when one is in close contact with unvaccinated people. Thus, family caregivers’ choices to remain unvaccinated against COVID-19 could have potentially lethal consequences for their relatives. To our knowledge, this study represents the first attempt within the international literature to analyze COVID-19 vaccine uptake among family caregivers of people with dementia and to identify some of the psychological factors, related to COVID-19 and vaccination behavior, that could facilitate or hinder vaccine uptake. Contact information for family caregivers was obtained from six different centers and associations throughout the national (Italy) territory. Data were collected from 179 respondents during July-September 2021 using a cross-sectional web-based survey design. More than 75% of the respondents indicated that had been vaccinated against COVID-19 and reported receiving vaccine information mainly from print or electronic newspapers (86%), followed by TV (81%) and families (64.2%). In multivariable logistic regression analyses, worries about unforeseen future effects was significantly related to COVID-19 vaccine uptake, indicating that family caregivers concerned about potential side effects of vaccines were less likely to have been vaccinated against COVID-19 (OR=0.60, CI=0.40-0.89). Openness to experience was also related to COVID-19 vaccine uptake, with family caregivers higher on this trait being less likely to have been vaccinated against COVID-19 (OR=0.83, CI=0.71-0.98). Implications for targeting of vaccine-related messages are discussed.